Amniotic fluid‐derived mesenchymal stem cell products combined with microneedling for acne scars: A split‐face clinical, histological, and histometric study. (7th June 2019) - El-Domyati, Moetaz; Moftah, Noha H.; Nasif, Ghada A.; Ragaie, Maha H.; Ibrahim, Michel R.; Ameen, Sameh W.
Abstract: Background: Postacne scars are still a challenge in its management. Microneedling is a popular minimally invasive technique in treatment of such scars. However, the addition of topical stem cell products after microneedling is considered a new treatment regimen for these scars. Objective: To compare efficacy of amniotic fluid‐derived mesenchymal stem cell‐conditioned media (AF‐MSC‐CM) and microneedling vs microneedling alone in management of atrophic acne scars. Methods: Ten cases with atrophic postacne scars received five sessions of microneedling, with 2‐week interval on both sides of the face. Then, AF‐MSC‐CM was topically applied to right side of the face after microneedling. Clinical examination with histopathological and computerized histometric analysis was done 1 month after the sessions. Results: There was significant increase in the improvement percentage of acne scars on right side (dermaroller and AF‐MSC‐CM) vs left side of face (dermaroller; P  < 0.001). Histologically, improvement of character of collagen and elastic fibers was noticed, especially on right side. Meanwhile, significant increase in epidermal thickness on both sides of face was detected. Conclusion: Amniotic fluid‐derived mesenchymal stem cell‐conditioned media combined with microneedling is more effective in management of atrophic postacne scars than microneedling alone.